Exploration of User Acceptance Level of I-Bontang Mobile Application Technology with Technology Acceptance Model (TAM) Approach at Bontang City Regional Library - Retno Febriaryanti; Amir Fikri; Maya Maria (PT. Publikasiku Academic Solution, 2023)
In the era of globalization, people are increasingly demanding to always want to get fast, cheap, comfortable, and precise services. As a service that runs library affairs, this phenomenon is a challenge for libraries to always make transformations in a better direction to maintain regional literacy levels. Therefore, this research was conducted to assess the factors of user acceptance of the application of the i-Bontang digital library system to users of Perpustakaan Daerah Kota Bontang. Based on the Technology Acceptance Model (TAM) framework, researchers analyzed the locus of perceived ease of use and perceived usefulness of various latent variables including behavior intention to use, actual system to use, relevance, subjective norms, screen design, mobility, trust in content, library assistance, computer literacy, trust in content, and level of infrastructure. Not only that, measurements were also carried out using Structural Equation Modeling (SEM) through the overall model fit test, validity test, and reliability test with a t-value > 1.96. The results of this study indicate that perceived ease of use is influenced by several variables such as screen design, mobility, librarian assistance, and computer literacy, while perceived usefulness is influenced by variables perceived ease of use, relevance, subjective norms, trust in content, and level of infrastructure. From this research it is proven that the actual system to use variable shows the strongest influence on the behavioral intention to use variable. In the end, the TAM model has helped assess the components in digital library acceptance with the hope that management in implementing systems such as i-Bontang can develop further.